THE ASSESSMENT OF POSTURE IN MYOFASCIAL PAIN DISORDERS OF THE TEMPOROMANDIBULAR SYSTEM - Figen Ardıç; Mukaddes Yılmaz; Nilgün Palulu; Müyesser Okumuş; Z. Rezan Yorgancıoğlu; Sibel Güner (Archives of Rheumatology, 2005)
Many clinicians have speculated that poor posture may have a negative effect on temporomandibular disorders (TMD), symptoms, and treatment outcome. The aim of this study was to analyse poor posture seen in primary miyofasyal TMD as clinically and radiologically. Forty-eight patients (mean age: 39.4 ±12.3, 45 female and 3 male) diagnosed with primary myofascial TMD according to the RDC/TMD described by Dworkin & LeResche were included in this study. Pain of the postural muscles in temporomandibular system, the types of poor posture, the level of depression, the results of double-aspects x-rays of cervical and thoracal spine and TMJ HRCT were recorded. Forward-drooping shoulder (85.4%) and forward-head posture (39.6%) were the most common faulty posture types in the postural analysis. Flattening of the cervical axis (58.3%) was observed most frequently . Upper trapezius has been interpreted as the most severely affected miyofasyal structure. As conclusion, poor posture is common in primary miyofasyal TMD and posture training may have critical importance.